Tibetan texts of “The Sutra of Eight Luminous of Heaven and Earth” kept in the manuscript collection of a Tuvan institute - Mirzaeva, Saglara V.; Muzraeva, Delyash N.; Bicheldey, Uliana P. (The New Research of Tuva, 2022)
The article analyzes and introduces the Tibetan-language texts of “The Sutra of Eight Luminous of Heaven and Earth” kept in the manuscript repository of the Tuvan Institute of Humanities and Applied Social and Economic Research under the Government of the Republic of Tuva. Among five texts (both xylographs and manuscripts) found in the collection, there are well-known versions A (included in Bka-′gyur) and B (included in the Gzungs-′dus collection), and also a summarized version of the sutra not found in Buddhist Digital Resource Center, the largest database of Tibetan texts. The analysis of this version shows that it can be related to version B of the sutra. The text entitled “Gnam sa snang brgyad kyi mdos bzhes bya ba bzhugs so” (‘Mdos ritual of “Eight Luminous of Heaven and Earth”’) is of particular interest because it contains the description of a special ritual with mdos (thread-cross). The introductory part of the text describes a visualization of supernatural beings invited for this ritual. The main text is an invocation to various spirits in four main and four intermediary directions. The spirits are supposed to accept this ransom offering (Tib. glud). The invocation is written in a poetic form organised as heptasyllabic verses. The manuscript ends with a list of attributes and offerings necessary for the ritual and an instruction how to organize them on the altar. According to the text, this ritual is aimed at aversion of various obstacles, mainly the astrological ones (bdun-zur). Besides, in the end of the work there are additional instructions on an illness-curing ritual performed on the basis of this text and a list of necessary attributes.